The Impacts of Inclusive Representation in Nepal - Guragain, Govinda Prasad (Rural Development Journal, 2019)
Nepal is a nation with a diverse population. This diversity spans various aspects such as race, ethnicity, religion, caste, and region. Historically, Nepal faced significant issues of social exclusion, resulting in numerous social, economic, and political inequalities. The interim constitution of Nepal (2063) aimed to address this by including provisions for the social inclusion of minorities and marginalized groups in national policies. This paper explores the inclusive representation of different groups and its impact on social, economic, and political spheres. The study relies on both primary and secondary information sources, focusing primarily on the effects of inclusive representation in Nepal. The government decided to reallocate quotas in civil service, reducing reservations for certain ethnic groups to maintain a quota cap of 45%. Specifically, it reduced the Madhesi quota from 22% to 20%, the Adiwasi/Janajati quota from 27% to 24%, and the quota for differently-abled individuals from 5% to 3%. Despite criticisms, the reservation system has positively impacted the participation of underprivileged and minority groups across various sectors.